2005
DOI: 10.1038/sj.eye.6701912
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma with orbital metastasis: ophthalmic presentation and role of ophthalmologists

Abstract: Introduction Neuroblastoma is predominantly a tumour of early childhood, which metastasises to the orbits. In such cases, ophthalmologists are involved in the multidisciplinary management. This unique series from a tertiary referral centre is used to elaborate the ophthalmic associations and the ophthalmologist's role in this rare condition. Methods A review of case notes was performed on six patients who presented to the paediatric ophthalmology -oncology liaison service at the Leeds teaching hospitals betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 6 publications
1
58
1
Order By: Relevance
“…Systemic chemotherapy may be helpful in the treatment of orbital and ocular adnexal metastases, especially from chemosensitive tumors, such as small cell lung cancer and neuroblastoma [22 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Systemic chemotherapy may be helpful in the treatment of orbital and ocular adnexal metastases, especially from chemosensitive tumors, such as small cell lung cancer and neuroblastoma [22 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The age at presentation is usually 15 months or later. Congenital neuroblastoma is rare, and fewer than 100 cases have been reported in the literature [2, 5, 6]. …”
Section: Discussionmentioning
confidence: 99%
“…3,4,12,14,17 With an incidence of approximately 1 in 7000 children younger than 5 years, [18][19][20][21] neuroblastoma is the most common extracranial solid tumor among children younger than 5 years, and rarely appears in children older than 10 years. 21 The absence of neuroblastoma underlying Horner syndrome in this study prompted a review of the Olmsted County medical records of the 21 pediatric patients with diagnoses of neuroblastoma during the same 40-year period, and none were found to have a concurrent Horner syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported minimal correlation between neuroblastoma and pediatric Horner syndrome. 4,5,18,[22][23][24] The relatively high number of occult malignancies among patients with Horner syndrome in some studies can be explained, at least in part, by referral bias. 3,4,[11][12][13][14] Another potential weakness of this study is that some patients may have sought care outside Olmsted County, thereby underestimating the incidence of Horner syndrome.…”
Section: Discussionmentioning
confidence: 99%